2014
DOI: 10.4236/eng.2014.65026
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties of Cement-Based Grouts Determined by Different Techniques

Abstract: The rheological properties of cement-based grouts containing talc or palygorskite were investigated for optimizing fluidity and quick strengthening at injection. The fluidity controls the ability of grout to penetrate fractures and can be determined by pipe flow tests, Marsh funnel tests, mini-slump cone tests and rheometer tests. The grouts were 1) Talc for fluidity and strength by reacting with cement, 2) Palygorskite (attapulgite) for early gelation by being thixotropic, and 3) Powdered quartz for chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Several authors have demonstrated the existence of correlations between the plastic viscosity and the Marsh cone flow time [25][26][27]. Other authors have shown, in an experimental way, that the comparison of the Marsh cone flow time and yield stress values at the saturation dosage are similar [22].…”
Section: Measurement Of Yield Stressmentioning
confidence: 99%
“…Several authors have demonstrated the existence of correlations between the plastic viscosity and the Marsh cone flow time [25][26][27]. Other authors have shown, in an experimental way, that the comparison of the Marsh cone flow time and yield stress values at the saturation dosage are similar [22].…”
Section: Measurement Of Yield Stressmentioning
confidence: 99%
“…The experiments highlight the role of the rheological properties and the filtering behaviour of certain grouts (Mohammed et al, 2014b). The following observations were drawn from the study of the low-pH cement-talc grout types:…”
Section: Grout In Fracture Zonesmentioning
confidence: 99%
“…Thus, accurate measurement of the grout rheological properties is of great importance. Therefore, several instruments and methods have been developed to measure grout properties, among which the Marsh funnel is the most common, applicable in both the lab and field in the construction and oil industries (Balhoff et al, 2011;Benaicha, Jalbaud, Hafidi Alaoui, and Burtschell, 2015;Guria, Kumar, and Mishra, 2013;Le Roy, 2004;Mohammed, Pusch, Knutsson, and Hellström, 2014;Nguyen, Rémond, Gallias, Bigas, and Muller, 2006;Pitt, 2000;Roussel and Le Roy, 2005;Schwarz, 1997). The Marsh funnel, developed in the late 1920s, is an orifice meter, that is, a simple draining cone under gravitational force without replenishment for measuring the viscosity of drilling mud, grout, and any sort of slurry or cement paste (Marsh, 1931).…”
Section: Introductionmentioning
confidence: 99%